2021
DOI: 10.1523/jneurosci.0851-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Axonal CB1 Receptors Mediate Inhibitory Bouton Formation via cAMP Increase and PKA

Abstract: Experience-dependent formation and removal of inhibitory synapses are essential throughout life. For instance, GABAergic synapses are removed to facilitate learning, and strong excitatory activity is accompanied by the formation of inhibitory synapses to maintain coordination between excitation and inhibition. We recently discovered that active dendrites trigger the growth of inhibitory synapses via CB1 receptor-mediated endocannabinoid signaling, but the underlying mechanism remained unclear. Using two-photon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 135 publications
(215 reference statements)
0
10
0
Order By: Relevance
“…[62][63][64] Recent evidence links PKA activity to synapse formation. 65,66 What could be the function of PKA-induced PLPPR3-BASP1 complex at the synapse?…”
Section: Molecular Mechanism and Function Of Plppr3-basp1 Complex At ...mentioning
confidence: 99%
“…[62][63][64] Recent evidence links PKA activity to synapse formation. 65,66 What could be the function of PKA-induced PLPPR3-BASP1 complex at the synapse?…”
Section: Molecular Mechanism and Function Of Plppr3-basp1 Complex At ...mentioning
confidence: 99%
“…Recent evidence, however, has shown that CB1R expressed on inhibitory axons promotes inhibitory boutons, triggered by increased cAMP levels and PKA activity (Liang et al, 2021). On the other hand, the CB2R is expressed in both neurons and microglial cells, and its activation modulates neuronal excitability and neuroinflammation, respectively (den Boon et al, 2012;Komorowska-Müller & Schmöle, 2020;Stempel et al, 2016).…”
Section: Endocannabinoid Signaling In Microgliamentioning
confidence: 99%
“…Further, GABA B receptor activation can impair axonal elongation (Bird and Owen, 1998;Ferguson and McFarlane, 2002;Xiang et al, 2002). Similarly, endocannabinoid CB1 receptors are highly expressed on developing corticofugal axons influencing growth cone collapse and proper targeting (Roland et al, 2014) and mediate formation and stabilization of GABAergic axonal boutons (Liang et al, 2021). Loss of CB1 receptor signaling evokes aberrant apical dendritic sprouts of migrating pyramidal neurons of the cortical plate, which impairs their migration (Díaz-Alonso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%